Full Control of Virtual Objects Manipulation Based on the Images of Real Ones - Nini, Brahim (International Journal of Virtual Reality, 2011)
This work deals with the virtual manipulation of a real object through its images. The results presented in this paper give a movie-based solution to the simulation process. We show how the simulation of infinite virtual views of a moving object can be reached using a finite number of object's taken images stored in an organized way. The basis of this solution is an analytical geometry-based method that links explicit applied user's actions, resulting in an object's views change, and images that match the best such views. This paper presents an overall solution for these three intertwined parts of the virtual manipulation that involves six degrees of freedom. Hence, a user is able to freely manipulate a virtual object in a scene in whatever manner s/he likes. In this case, the actions are transformed into rotations and/or translations which lead to some changes in object's appearance, both covered by two viewing features: zoom and/or rotations